Waladuzzina Wa Ahkamuhu Dirasah Mugaranah Bain Asyri'h Wal Gunun - Al shehabi, Ahmed ali (2016)
ولد الزنا وأحكامه (دراسة مقارنة بين الشريعة والقانون اليمني والإندونيسي) الملخص هذه الرسالة بحث مكتبي كيفي, يعتمد المنهج التحليلي النقدي المقارن, لقضية ولد الزنا وأحكامه في الشريعة والقانون اليمني والاندونيسي,ومشكلة البحث تدور حول النقاط التالية: 1- ما هي نظرة الشريعة الإسلامية إلى ولد الزنا ؟ 2- هل حفظ الإسلام لولد الزنا حقوقه الشرعية كما حفظها لغيره من الأولاد الشرعيين ؟ 3- أيهما اشد اهتماما و أبعد نظراً لمشكلة ولد الزنا, الشريعة الإسلامية أم القوانين الوضعية ؟ بعد البحث في النصوص الشرعية و كتب علماء المذاهب الفقهية ومقارنتها بكل من القانون اليمني والإندونيسي فقد توصل الباحث إلى أن الشريعة الإسلامية حفظت لولد الزنا حقوقه وكرامته ومنزلته بين الناس, ولم تحمله من وزر والديه شيئ, والأحاديث والنصوص التي وردت وظاهرها يدل على ذم ولد الزنا واحتقاره إما أن تكون ضعيفة الإسناد أو أنها مقيدة بأشخاص معينين. وأن ولد الزنا كغيره من الأولاد الشرعيين في جميع الأحكام والحقوق إلا في قضية النسب وما يتعلق به, فإن الشريعة أفردت له أحكاماً خاصة به تتناسب معه ومع محيطه الإجتماعي.كما أن الشريعة الإسلامية هي الحامية الأولى لحقوق الشعوب ومصالحهم, وكلاً من القانون اليمني والإندونيسي لم يستوف أحكام ولد الزنا كاملة, مما يدل على ضعف القدرة البشرية عن إدراك المصالح والحقوق. الكلمات الرئيسية : ولد - الزنا - أحكام - مقارنة - الشريعة - القانون - اليمني- الاندونيسي Illegitimate child and rulings (Comparative study between Sharia law and the Yemeni and Indonesian) Abstract This message qualitative desk research, analytical approach depends comparative cash, the issue of illegitimate child and its provisions in the law and the Yemeni and Indonesian law, and the research problem revolves around the following points: 1. What is the view of Islamic law to the illegitimate child? 2. Does the Name of Islam to the illegitimate child of his rights as legitimate saved for other children of immigrants? 3. Which is more interested in and beyond due to the problem of illegitimate child, the Islamic Sharia or man-made laws? After searching in religious texts and books schools of Islamic jurisprudence scholars and comparing each of the Yemeni law and Indonesian researcher reached the following conclusions: 1. Islamic law preserved the illegitimate child of his rights, dignity and stature among the people, and did not bear the brunt of his parents something, conversations and texts received and seemingly shows to condemn the illegitimate child and contempt are either weak or cross it restricted certain people. 2 - the illegitimate child of immigrants, like the boys in all the provisions and rights except in the case of percentages and related, the law has devoted its special provisions commensurate with him and his social surroundings. 3. Islamic law is the first of the Protecting the rights of peoples and interests, and both the Yemeni and Indonesian law does not meet the provisions of the boy full of adultery, which shows the weakness of the human capacity to recognize the interests and rights.